Paroxysmal headache with extracephalic irradiation: Proposal for a new variant of epicrania fugax in a series of five patients. (August 2020) - Gutiérrez-Sánchez, María; García-Azorín, David; Gutiérrez-Viedma, Álvaro; González-García, Nuria; Horga, Alejandro; Martín, Susana; Guerrero, Ángel L; Cuadrado, María-Luz
Background: Epicrania fugax consists of brief paroxysms of pain, which radiate in a line or in zigzag trajectory across the surface of the scalp or the face. Methods: A prospective, descriptive study was performed in five patients presenting with an epicrania fugax-type pain with extracephalic irradiation. Results: All patients were women, and the mean age at onset was 59.8 (standard deviation, 10.9). They had unilateral paroxysms of electrical pain starting at a particular point in the head (parietal, n = 3; vertex, n = 1; frontal, n = 1) and rapidly radiating downwards in a lineal trajectory to reach extracephalic regions (ipsilateral limbs, n = 2; shoulder, n = 2; low neck, n = 1) in 1–3 seconds. Pain intensity was moderate or severe. Three patients had nummular headache at the point where the paroxysms originated. One patient had spontaneous remission, and four patients achieved complete or almost complete response with therapy (onabotulinumtoxinA, n = 2; indomethacin, n = 1; amitriptyline, n = 1; lamotrigine, n = 1). Conclusion: The spectrum of epicrania fugax may include paroxysms with extracephalic irradiation. The propagation of pain beyond the head and the face supports the involvement of central mechanisms in the pathophysiology of this entity.